Early life factors for myopia in the British Twins Early Development Study. Issue 8 (6th November 2018) - Williams, Katie M; Kraphol, Eva; Yonova-Doing, Ekaterina; Hysi, Pirro G; Plomin, Robert; Hammond, Christopher J
Abstract : Purpose: Myopia is an increasingly prevalent condition globally. A greater understanding of contemporaneous, early life factors associated with myopia risk is urgently required, particularly in younger onset myopia as this correlates with higher severity and increased complications in adult life. Methods: Analysis of a subset of the longitudinal, UK-based Twins Early Development Study (n=1991) recruited at birth between 1994 and 1996. Subjective refraction was obtained from the twin's optometrists; mean age 16.3 years (SD 1.7). Myopia was defined as mean spherical equivalent ≤−0.75 dioptres. A life course epidemiology approach was used to appropriately weight candidate myopia risk factors during critical periods of eye growth. Adjusted ORs for myopia were estimated using multivariable logistic regression models at each life stage, together with variance explained (r 2 ) and area under the receiver operator characteristic curve (AUROC) statistic of predictive models. Results: Factors significantly associated with myopia included level of maternal education (OR 1.33, 95% CI 1.11 to 1.59), fertility treatment (OR 0.63, 95% CI 0.43 to 0.92), summer birth (OR 1.93, 95% CI 1.28 to 2.90) and hours spent playing computer games (OR 1.03, 95% CI 1.01 to 1.06). The total variance explained by this model was 4.4 % (p<0.001) and the AUROC was 0.68 (95% CI 0.64 to 0.72). Consistent associations were observed with socioeconomic status, educational attainment, reading enjoyment and cognitive variables, particularly verbal cognition, at multiple points over the life course. Conclusions: This study identifies known and novel associations with myopia during childhood development; associated factors identified in early life reflect sociological and lifestyle trends such as rates of maternal education, fertility treatment, early schooling and computer games.